m6A in mRNA coding regions promotes translation via the RNA helicase-containing YTHDC2 - Yuanhui Mao (Nature Portfolio, 2019)
Several functions have been proposed for m6A in RNA metabolism, yet little is known regarding the specific functions of individual m6A readers. Here, the authors observe that the m6A reader YTHDC2 — which contains an RNA helicase domain — acts on the coding region to promotes mRNA translation by resolving secondary structures.